2003
DOI: 10.1046/j.1439-0272.2003.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Male factors determining the outcome of intracytoplasmic sperm injection with epididymal and testicular spermatozoa

Abstract: During a period of 8 years, 1,079 intracytoplasmic sperm injection (ICSI) procedures with aspirated epididymal or testicular spermatozoa were performed. Epididymal spermatozoa were used in 172 cycles and testicular spermatozoa or spermatids in 907 cycles. Multiple biopsies were obtained from at least two different locations in the testes. Retrieved spermatozoa were used after cryopreservation (frozen) or immediately after aspiration (fresh). Three hundred patients had obstructive azoospermia (OA) or ejaculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 12 publications
2
17
1
2
Order By: Relevance
“…Defective spermatogenesis can be observed in patients with normal FSH levels, and as a known fact in the presence of very high FSH levels, motile spermatozoa can be retrieved. [17] Also in our study, in 2 patients with FSH levels of 41.6, and 60 mIU/mL, respectively, sperm retrieval could be achieved during TESE. In a study by Schwarzer et al [17] in the year 2003, 414 NOA patients were grouped according to FSH levels of 0-10, 10-20, 21-30, 31-40 ve 40 mIU/mL, and a statistically significant TESE-positivity was not detected between groups.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Defective spermatogenesis can be observed in patients with normal FSH levels, and as a known fact in the presence of very high FSH levels, motile spermatozoa can be retrieved. [17] Also in our study, in 2 patients with FSH levels of 41.6, and 60 mIU/mL, respectively, sperm retrieval could be achieved during TESE. In a study by Schwarzer et al [17] in the year 2003, 414 NOA patients were grouped according to FSH levels of 0-10, 10-20, 21-30, 31-40 ve 40 mIU/mL, and a statistically significant TESE-positivity was not detected between groups.…”
Section: Discussionsupporting
confidence: 56%
“…[17] Also in our study, in 2 patients with FSH levels of 41.6, and 60 mIU/mL, respectively, sperm retrieval could be achieved during TESE. In a study by Schwarzer et al [17] in the year 2003, 414 NOA patients were grouped according to FSH levels of 0-10, 10-20, 21-30, 31-40 ve 40 mIU/mL, and a statistically significant TESE-positivity was not detected between groups. However in our study when FSH levels of patients were grouped as 0-10, 11-20, 21-30, and >30 mIU/mL, a statistically significant difference was detected between groups.…”
Section: Discussionsupporting
confidence: 56%
“…With conventional TESE (3-10 biopsies), the retrieval rate was 60%. 16 In our current cohort, 49% of the 220 patients had a histological diagnosis of SCOS or tubular sclerosis, and the overall sperm retrieval rate was 58%, despite the additional use of M-TESE. Compared with our previous cohort from 2003, we encountered a substantial increase in unfavourable prognostic factors in our patients.…”
Section: Resultsmentioning
confidence: 67%
“…Recent studies reported that, although testicular histopathology is the strongest predictor of sperm retrieval in men with NOA, testicular histopathology does not have any influence on outcome of microdissection TESE for ICSI [Abdel Raheem et al 2013;Karacan et al 2013]. However, TESE performed via an open biopsy is an effective and reliable technique for retrieving spermatozoa, with generally successful spermatozoa recovery rates in patients with NOA [Wood et al 2002;Schwarzer et al 2003;Giorgetti et al 2005]. For testicular spermatozoa retrieval, we used the two fine forceps method; the advantage of this method is that damage can be prevented that could occur by germ cells mixing with tissue particles, blood vessels, as well as by exposure of spermatogenic cells to a harmful environment during handling of the testicular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The cleavage stage rates and implantation rates were also not different between any of these groups. Moreover, the fertilization rates (FRs) were not different between the various NOA subgroups when spermatozoa extraction was successful; importantly, successful embryo transfer in these groups has also been demonstrated [Schwarzer et al 2003]. However, to our knowledge, there have been no reports comparing the rates of fertilization, good quality embryos, clinical pregnancy, and delivery using fresh and frozen-thawed testicular spermatozoa from patients in each of the NOA subgroups (HS, MA, and SCO).…”
Section: Discussionmentioning
confidence: 99%